Modern approaches of the cerebral palsy pathogenesis in the substantiation of program for its early diagnosis and treatment introduction - L. A. Anaeva (Кубанский научный медицинский вестник, 2015)
It was performed the literature data analysis on the mechanisms of cerebral palsy (CP). Presents current information about the processes of the brain differentiation considered the pathogenesis of lesions that underlie the clinical manifestations of the CP. Understanding the processes intensively in the central nervous system is essential for the early diagnosis of disease among children in this age group received to date data indicate that the major activities for the early diagnosis and early treatment of perinatal pathological changes should be carried out in the prenatal period and during the first year a child's life.